Peran Permainan Dalam Meningkatkan Kreatifitas Anak Usia Dini Umur 4-6 Tahun - Hasanah, Iklimatul (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2023)
Children's creativity is likely to grow and develop, so that creativity in early childhood increases, appropriate games are needed. The aim of this research is to increase the creativity of early childhood children aged 4-6 years through play. The method used in this research is the Systematic Literature Review (SLR) method. The research results obtained state that the role of games in increasing the creativity of children aged 4-6 years is very important. The creativity of children aged 4-6 years can be increased through color games, Lego games, magic puffle ball games, and construction games.